Sufism of Archipelago: History, Thought, and Movement - Syaifan Nur; Dudung Abdurahman (UIN Sunan Kalijaga Yogyakarta, 2017)
The development of Islam tend to shows the diversity according to the age and socio-cultural region of its adherents. This is the case with the development of Islam in the archipelago, which shows a diversity in the pattern of development of the teachings and religious aspects, along with the diversity of its society which includes various ethnicities and cultures. One such pattern of Islam is Sufism, the Islamic aspect which emphasizes the inner or esoteric aspects, based on the Sufi doctrine and comprehension. This paper focuses on the development of Sufism in the archipelago, viewed in terms of history, thought, and tarekat movements. The archipelago Sufism is studied in historical and socio-anthropological perspectives. Broadly speaking, it can be stated that Firstly, in the process of Islamization of the archipelago, Sufism acts as a media of Islamic society carried out by the Sufi in their preaching about the XIII century until the XVI century; Second, the development of Sufism in the archipelago in the XVII century until the XIX century experienced a shift in the pattern of development, role and movement. Their role is mainly to establish the spiritual aspect of religious life and development, but through the power and social communities of the tarekat they can also carry out social movements, especially in mobilizing the people’s struggles against Dutch colonialism in the nineteenth century. Finally, the Sufism of Nusantara (Archipelago) that is netted in tarekat movements continues to show its wider role in the twentieth century. Some tarekat communities not only maintain religious traditions that are spiritual, but also work in education, economics, and politics. Thus, the contribution of sufism is very beneficial to society in general, both in order to fulfill their spiritual needs and worldly life.[Perkembangan Islam selalu menunjukkan keragaman sesuai zaman dan wilayah sosial-budaya masyarakat pemeluknya. Sebagaimana Islam di Nusantara menunjukkan keragaman pola pengembangan ajaran dan aspek keagamaan itu adalah seiring masyarakatnya yang meliputi beragam etnis dan budaya. Salah satu pola keislaman tersebut adalah sufisme, yakni aspek keislaman yang lebih menekankan segi batiniah atau esoterik berdasarkan faham dan ajaran para Sufi. Tulisan ini memfokuskan pembahasannya tentang perkembangan sufisme di Nusantara, baik dilihat dari segi sejarah, pemikiran, maupun gerakan-gerakan tarekat. Sufisme Nusantara tersebut dipelajari dalam perspektif sejarah dan sosio-antropologis. Secara garis besar dapat dinyatakan, bahwa Pertama, dalam proses islamisasi Nusantara, sufisme berperan sebagai media pengislaman masyarakat yang dilakukan oleh para sufi dalam dakwahnya pada sekitar abad XIII hingga abad XVI; Kedua, Perkembangan sufisme di Nusantara pada abad XVII hingga abad XIX mengalami pergeseran pola pengembangan, peranan maupun gerakannya. Peranan mereka yang terutama memantapkan aspek spiritual bagi kehidupan dan perkembangan keagamaan, tetapi melalui kekutaan serta komunitas sosial tarekat juga mereka dapat melakukan gerakan sosial, khususnya gerakan-gerakan sosial yang dimobilisasi seiring perlawanan-perlawanan rakyat Nusantara terhadap kolonialisme Belanda pada abad XIX. Ketiga, Sufisme Nusantara yang terjaring dalam gerakan-gerakan tarekat terus menunjukkan peranannya yang lebih luas pada abad XX. Beberapa komunaitas tarekat bukan hanya mempertahankan tradisi keagamaan yang bersifat spiritual, melainkan juga bergerak di bidang pendidikan, ekonomi, dan politik. Dengan demikian, kontribusi sufisme akan sangat bermanfaat bagi masyarakat pada umumnya dalam rangka pemenuhan kebutuhan ruhaniah mereka.]